ECONOMIC, SOCIAL, CULTURAL CONDITIONS OF FORMATION OF VIEWS OF MEDIEVAL THINKERS - Tursunoy Abduvokhid kizi Abdurakhimova (Journals Park Publishing, 2023)
In this article, the world-famous scientists who were engaged in various sciences in the Middle Ages and enriched them with new discoveries, their contribution to various fields of science (economic, social, natural, concrete, cultural) and the conditions created for them will be explained.
Keywords: renaissance, spiritual purification, feudal disunity, mathematics, observatory, culture, justice.